2021
DOI: 10.1007/s11356-021-15275-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and corporate factors and COVID-19 pandemic: a wake-up call

Abstract: The novel coronavirus 2019 (COVID-19) emerges from the Chinese city Wuhan and its spread to the rest of the world, primarily affected economies and their businesses, leading to a global depression. The explanatory and cross-sectional regression approach assesses the impact of COVID-19 cases on healthcare expenditures, logistics performance index, carbon damages, and corporate social responsibility in a panel of 77 countries. The results show that COVID-19 cases substantially increase healthcare expenditures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Subsidized trade policies would be beneficial in reviving the stock market and economic activity in the aftermath of the COVID-19 epidemic [ 72 , 73 ]. Continued economic transactions of goods and services within and outside the country would desensitize the adverse economic consequences of a COVID-19 pandemic [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsidized trade policies would be beneficial in reviving the stock market and economic activity in the aftermath of the COVID-19 epidemic [ 72 , 73 ]. Continued economic transactions of goods and services within and outside the country would desensitize the adverse economic consequences of a COVID-19 pandemic [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…For curbing the COVID‐19 pandemic, Anser et al (2021) suggest several points for not interrupting the global healthcare supply chain, improving sustainable healthcare logistics activities, improving green supply chain processes, and the need for medical device transportation. Of course, effective policies do not end there; there are additional socioeconomic and environmental obligations that we must undertake.…”
Section: Response Strategies For Logistics In Various Fieldsmentioning
confidence: 99%
“…To prevent the rapid spread of new outbreaks, governments across countries have put in place stringent measures that have put global supply chains at risk of serious disruptions, leading to severe shortages of essential goods such as biological drugs, and have also exposed the opacity of logistics processes and low elasticity of supply and demand for timely and sustained production (Kovács & Falagara Sigala, 2021). Anser et al (2021) found that COVID-19 increased healthcare expenditures and decreased corporate social responsibility (CSR), while increased coronavirus detection capacity reduced healthcare expenditures, boosted logistics activities, and increased CSR. The expanded coronavirus testing capability has lowered healthcare costs, increased logistics, and improved CSR.…”
Section: Impacts On Healthcare Logisticsmentioning
confidence: 99%
“…Economic disparities are especially likely to result not only in distinct transmission and infection risks among hosts, but also in variable public health attention and responses [ 9 , 17 , 34 , 38 , 57 , 88 , 122 ]. The lack of pharmaceutical interventions, and the heavy reliance on underfunded, or structurally adjusted, public institutions for disease control may exacerbate existing disparities in vulnerability to infection among host populations [ 4 , 22 , 79 , 120 , 129 ]. This is because non-pharmaceutical interventions, ranging from highly targeted case-detection and expansive contact-tracing to population-wide guidelines on physical distancing to lockdowns and economic shutdowns, require both a robust public health infrastructure and high social and economic development to implement successfully [ 9 , 33 , 40 , 46 , 48 , 53 , 54 , 71 , 87 , 137 , 141 ].…”
Section: Introductionmentioning
confidence: 99%